PRENTICE MODEL TO PREDICT GESTATIONAL DIABETES MELLITUS ON THE BASIS OF MATERNAL RISK FACTORS: A CROSS-SECTIONAL STUDY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Objective: The aim of this study was to develop a predictive model of gestational diabetes mellitus (GDM) using the Prentice-weighted logistic regression method and assessing the contribution of significant maternal risk factors.